Histopathological correlations of bulk tissue polarimetric images: Case study. Issue 5 (13th February 2021) - Sharma, Mahima; Narayanan Unni, Sujatha; Balasubramanian, Subalakshmi; Sundaram, Sandhya; Krishnamurthy, Priya; Hegde, Anoosha
Abstract: Polarimetric imaging and image analysis have gained increased interest in soft tissue analysis at the cellular level. However, polarimetric imaging has widely been tested on thin tissue sections to provide reliable information correlated with histopathological findings. Polarimetric bulk tissue analysis always offered an overall assessment of various tissue optical properties for diagnosis. In this study, the histopathological correlation of bulk tissue polarimetry images for soft tissues is discussed. The first‐hand information on the use of bulk tissue Mueller polarimetry and image analysis as an alternative to tissue histopathology is presented for surgically extracted colon and breast tissues. Abstract : Correlating the tissue polarimetric information derived by Mueller polarimetry with the histopathological findings can facilitate diagnosis during perioperative tumor removal. The first‐hand information on the use of bulk tissue Mueller polarimetry and image analysis as an alternative to tissue histopathology is presented here for surgically extracted colon and breast tissues.